An Examination of the Perceived Countermeasure of Breath Alcohol Ignition Interlock Device and Behavioral Intention of Drunk Driving in South Korea: An Application of the Theory of Planned Behavior - Gyo, Jeong, Shin- (International Journal of Membrane Science and Technology, 2023)
In regulating drunk drivers, car-centered prevention seems to be more effective than driver-centered one. Breath Alcohol Ignition Interlock Device (BAIID) seems to be particularly promising countermeasure to drunk driving. However, the tool has not been adopted in South Korea yet. This study is examines effect of perceived countermeasure of BAIID on intention to behave drunk driving. This study predicts the behavioral intention to engage in drunk driving through the planned behavior theory. Subjects (N=286) are adults between the ages of 19 and 60 years. We constructed 20 items to measure the composition of the extended model of TPB. Demographic variables include gender and age. Results from hierarchical multiple regression indicate that (1) the model explains 28.2% of the total variance in intention and (2) attitude, subjective norm, and perceived BAIID are significant independent predictors of behavioral intention